India's neighbourhood : challenges in the next two decades - Dahiya, Rumel; Behuria, Ashok K.; Institute for Defence Studies and Analyses (New Delhi : Pentagon Security International, 2012)
Contributed articles.
"Institute for Defence Studies & Analyses, New Delhi."
Includes bibliographical references and index.
Keywords: India -- Foreign relations -- 21st century